Шляхи комерціалізації об’єктів інтелектуальної власності на машинобудівних підприємствах та протидії контрафакту - Ілляшенко, Сергій Миколайович; Орлов, П. А.; Гриньова, В. М. (НТУ "ХПІ", 2014)
Розглянуто стан та умови здійснення інноваційної діяльності на машинобудівних підприємствах України. Обґрунтовано основні напрямки комерціалізації об’єктів інтелектуальної власності, серед яких особлива увага приділена ліцензуванню інтелектуальних технологій та власному використанню результатів інноваційної діяльності. Показано, що максимальний економічний ефект машинобудівні підприємства можуть отримати лише при раціональному поєднанні як власного споживання, так і ринковій дистрибуції інтелектуальних технологій при максимальній протидії контрафактній діяльності.

The state's circumstances and innovation in machine-building enterprises of Ukraine. The basic directions of commercialization of intellectual property, including an emphasis on licensing technology and intellectual proper use of innovation. It is shown that the maximum economic benefit engineering companies can get only the rational combination of both domestic consumption and market distribution at maximum intelligently against counterfeit activity. The transfer of exclusive rights to the use of scientific and technological achievements, inventions, trademarks, software and other results of intellectual activities on the basis of license agreements - one of the most effective forms of commercialization of intellectual property. The final choice of routes, strategies and various forms of commercialization of intellectual property, of course, determined by the dynamics of technology updates, and other features of the various sectors of the economy. An effective mechanism for the development, distribution and consumption of intellectual property (transfer and commercialization processes) is impossible without the development and implementation of effective measures against counterfeit perpetrators of an exclusive right that nullify the lengthy and costly scientific research units of industrial enterprises, universities, research institutions and organizations.
Ways commercialization of intellectual property on machine-building enterprises and combating counterfeiting
Keywords: інноваційна діяльність; економічний ефект; вигоди; збитки; innovation; intellectual property commercialization; engineering enterprises; counterfeiting; economic impact